2012
DOI: 10.1016/j.healun.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative and post-operative risk factors associated with neurologic complications in patients with advanced heart failure supported by a left ventricular assist device

Abstract: BACKGROUND Neurologic complications (NCs) are the major adverse events after left ventricular assist device (LVAD) surgery. Pre-operative and post-operative factors associated with NCs in patients with LVADs were investigated. METHODS We reviewed 307 consecutive patients undergoing LVAD surgery (167 HeartMate I and 140 HeartMate II devices) at Columbia University Medical Center between November 2000 and December 2010. Clinical characteristics and hemodynamic and laboratory indexes were analyzed. NC was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 23 publications
1
71
0
1
Order By: Relevance
“…We reported recently that patients with postoperative infection are more prone to develop stroke than those without infection after LVAD implantation. 9 Infection precipitates coagulation abnormalities that may lead to a high frequency of LVADrelated thrombus formation resulting in right hemispheric stroke. Limitation of this study is that it is a single-center, retrospective analysis in a small cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported recently that patients with postoperative infection are more prone to develop stroke than those without infection after LVAD implantation. 9 Infection precipitates coagulation abnormalities that may lead to a high frequency of LVADrelated thrombus formation resulting in right hemispheric stroke. Limitation of this study is that it is a single-center, retrospective analysis in a small cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation protocol included heparin, warfarin, and antiplatelet agents, such as aspirin and/or dipyridamole, except for those patients with contraindication to the medication or/and active bleeding. 9 Clinical characteristics, postoperative infection frequency, and anticoagulant status associated with right and left hemispheric stroke were compared. We excluded bilateral and vertebrobasilar stroke from the comparison analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the greater the amount of time supported by a CF-LVAD, the greater the risk of developing a PSI. 6 Several studies have reported an association between infection and cerebrovascular events (CVEs) in patients supported with LVADs, [7][8] and we recently reported that persistence of bacteremia greater than 72 hours is a crucial distinguishing factor. 9 We recently reported a 7-fold increase in CVEs in patients with HeartMate-II (HMII) devices who have persistent Pseudomonas aeruginosa bloodstream infections.…”
Section: Complications Of Infectionmentioning
confidence: 99%
“…32 Infection leading to bacteremia and septic emboli are added mechanisms specific to VAD patients due to their high prevalence of chronic infections. 33 Bacteremia is associated with a > 8-fold increase in risk of stroke. 34 Inflammatory activation and lack of pulsatility impacting endothelial function in the cerebral circulation could have a significant role but has not been studied.…”
Section: Cerebral Functionmentioning
confidence: 99%